The BCIM economic corridor and Chinese investments in Myanmar: Asia prospect - Senz, Anja-Désirée (T.notes, 2017)
Asia's regionalization trend led to the formulation of numerous economic cooperation initiatives. These, however, often lack a clear implementation strategy.
Gesehen am 08.08.2019